Terapi Komplementer Akupresur Menurunkan Gejala Emesis Gravidarum Pada Ibu Hamil - Samsinar Samsinar; Yusda Seman (Oksitosin : Jurnal Ilmiah Kebidanan, 2024)
During pregnancy, nausea and vomiting become serious problems, especially reaching extreme levels called emesis gravidarum. Pregnant women try to overcome this problem by using medicines or complementary therapies such as acupressure. This research aims to evaluate the effectiveness of complementary acupressure therapy in reducing the symptoms of emesis gravidarum in pregnant women. A study involving 40 pregnant women, of which 20 experienced significant symptoms, used acupressure techniques at pericardium point 6 to relieve symptoms of nausea and vomiting during the early trimester of pregnancy. This research used quasi-experimental methods (pre-test and post-test) and collected data through questionnaires RINVR and observations at Posyandu Mattirotappareng 1, Tempe District, Wajo Regency, South Sulawesi Province. The results showed a significant difference in the frequency of nausea and vomiting before and after acupressure therapy. After undergoing therapy, there was a significant reduction in the average number of nausea and vomiting events per day, decreasing from 9.0 to 5.2 times. The p-value < 0.05 indicates that acupressure therapy has a significant impact in reducing the frequency of nausea and vomiting in pregnant women. Therefore, the use of acupressure therapy at pericardium point 6 as a non-pharmacological treatment option is effective in reducing symptoms in pregnant women during the early trimester of pregnancy.